1998
DOI: 10.3171/foc.1998.4.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of carboplatin (CBDCA) in progressive low-grade gliomas

Abstract: In this study, the authors sought to investigate the response rate and toxicity of carboplatin in patients with progressive low-grade glioma (LGG). Thirty-two patients with progressive LGG were treated with carboplatin at a dosage of 560 mg/m2. Treatment was given at 4-week intervals and continued until the disease progressed, unacceptable toxicity supervened, or for 12 additional courses after achieving maximal response. Patients with stable disease were treated with a total of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Radiation therapy can give long-term disease stabilization in some cases. Treatment with carboplatin, alone or combined with vincristine, has been reported to achieve durable disease stabilization in patients with primary or recurrent low-grade gliomas, even in young children who were asymptomatic with widespread neuraxis disease7,12,13). The overall prognosis for patients with leptomeningeal dissemination at the time of recurrence appears to be worse than the prognosis for patients with a localized recurrence, and far better than for patients with a malignant brain tumor with dissemination3,10).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy can give long-term disease stabilization in some cases. Treatment with carboplatin, alone or combined with vincristine, has been reported to achieve durable disease stabilization in patients with primary or recurrent low-grade gliomas, even in young children who were asymptomatic with widespread neuraxis disease7,12,13). The overall prognosis for patients with leptomeningeal dissemination at the time of recurrence appears to be worse than the prognosis for patients with a localized recurrence, and far better than for patients with a malignant brain tumor with dissemination3,10).…”
Section: Discussionmentioning
confidence: 99%
“…47,48 In their study, Packer et al reported a progression-free survival of 75% at 2 years and 68% at three years; 48 however, subsequent studies using carboplatin-based regimens have shown variable success. [49][50][51][52][53][54] The carboplatin regimens are not associated with major toxicity and appear relatively well tolerated although neutropaenia, thrombocytopaenia and allergic reactions may occur. Other chemotherapeutic agents that have been used in treating optic gliomas include temozolomide 55,56 and a five-drug regimen combination, abbreviated to TPDCV, that comprised 6-thioguanine, procarbazine, didromodulcitol, 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosurea (CCNU) and vincristine.…”
Section: Chemotherapymentioning
confidence: 99%
“…39 Although other chemotherapy regimens have demonstrated efficacy against low-grade gliomas, the Packer regimen remains the most commonly used course of therapy. 31,37,50,57,60 …”
Section: Chemotherapy For Opgsmentioning
confidence: 99%